INTERNATIONALIZATION OF REGIONAL UNIVERSITIES: DESIGNING PROGRAMMES FOR MASTER’S DEGREES IN HUMANITIES - I. E. Abramova; A. V. Ananyina (Высшее образование в России, 2018)
As international competition in education is growing, Russia needs to develop a strategy for enhancing the internationalization of its education system and attracting more international students. This task is especially pressing for regional pillar universities. The paper describes the experimental course aimed at teaching Russian teachers of humanities to design master’s programmes in English for international students, analyzes the encountered problems, and offers possible ways to solve them. The authors identify a specific “cross-academic barrier” to effective teacher-student communication in English, as well as a number of teacher’s functions aimed at overcoming this barrier. Special focus is placed on teacher functioning as an adapter and mediator, which is essential for effective interaction with foreign students. The authors also give practical recommendations for tackling professional problems which may arise during the process of designing master’s programmes in English. In conclusion the paper states the necessity of Russian teachers’ second language socialization in order for them to psychologically adapt to the specific conventions and practices of academic communication in English.